2020
DOI: 10.6004/jnccn.2019.7525
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Perceptions of Treatment Goals and Psychological Distress in Patients With Advanced Cancer

Abstract: Background: Studies have shown gaps in prognostic understanding among patients with cancer. However, few studies have explored patients’ perceptions of their treatment goals versus how they perceive their oncologist’s goals, and the association of these views with their psychological distress. Methods: We conducted a cross-sectional study of 559 patients with incurable lung, gastrointestinal, breast, and brain cancers. The Prognosis and Treatment Perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…25,28 Alternatively, patients' report that their illness is likely curable may reflect their goals and wishes for cure, even if they cognitively understand that their cancer is incurable. 29 In our study, patients' report that their oncologist told their them cancer was incurable was not associated with QOL or psychological distress. However, acknowledgment of terminal illness was associated with higher psychological distress, symptom burden, and lower QOL in patients with MM.…”
Section: Discussionmentioning
confidence: 55%
“…25,28 Alternatively, patients' report that their illness is likely curable may reflect their goals and wishes for cure, even if they cognitively understand that their cancer is incurable. 29 In our study, patients' report that their oncologist told their them cancer was incurable was not associated with QOL or psychological distress. However, acknowledgment of terminal illness was associated with higher psychological distress, symptom burden, and lower QOL in patients with MM.…”
Section: Discussionmentioning
confidence: 55%
“…Equally important is the incorporation of a patient’s prognostic awareness of their disease. There is often a mismatch between a patient’s treatment expectations and their oncologist’s expectations [ 10 ]. Ongoing patient-provider communication can help to inform patient-centered treatment modifications especially when a patient is at a new treatment decision point, when the cancer recurs or progresses.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining patients' perception of treatment goals showed that patients who acknowledged the incurable nature of their disease reported higher psychologic distress compared with those who perceived their treatment goals as curative, regardless of accuracy of the perception. 13 Additionally, patients whose treatment goals were discordant with their oncologist's also reported increased distress symptoms. 13 In contrast, another study showed that patients with an accurate understanding that their disease was incurable who engaged in specific active coping strategies had fewer depressive symptoms than those not engaged in coping strategies.…”
Section: Palliative Care In Oncologymentioning
confidence: 99%
“…13 Additionally, patients whose treatment goals were discordant with their oncologist's also reported increased distress symptoms. 13 In contrast, another study showed that patients with an accurate understanding that their disease was incurable who engaged in specific active coping strategies had fewer depressive symptoms than those not engaged in coping strategies. 14 The panel recommends encouraging adaptive coping methods for patients, family, and caregivers, particularly when cultivating prognostic awareness to help improve both goal-concordant care and QoL.…”
Section: Palliative Care In Oncologymentioning
confidence: 99%